PERTANGGUNGJAWABAN PIDANA KORPORASI SEBAGAI PELAKU TINDAK PIDANA PENYEBARAN DATA PRIBADI - Denta Putra Azhar; Ahmad Mahyani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The existence of criminal acts of spreading personal data that occurred in Indonesia is becoming increasingly high in development, where not only the perpetrators are individuals but also the perpetrators are companies or corporations. But in reality law enforcement still cannot touch criminal acts where the perpetrators are corporations, especially those who are held accountable under criminal law. The problems raised by the author are: 1) What is the criminal responsibility of the corporation as the perpetrator of the criminal act of corruption in the case. The approach method in research is normative juridical with a qualitative nature and uses data sources in the form of secondary data. The author gives the opinion that the appropriate form of criminal responsibility is the imposition of aspects of responsibility that are criminal in nature against the corporation and also the management of the corporation, which will then lead to a deterrent effect for corporations not to commit criminal acts